The Influence of Corporate Social Responsibility and Tourism Development Towards Regional Financial Independence and Regional Development in Berau District - La Ode Ilyas; Rochaida, Eny; Suharto, Rahcmad Budi (International Journal of Economics (IJEC), 2023)
The aim of the research is to test the truth of regional development theories, namely firm location theory and new economic geography theory, as well as functional development theory, with the research object being the PT company. Berau Coal, in Berau district, East Kalimantan province. Recommends the results of research, namely the corporate social responsibility program and tourism development towards regional financial independence and regional development in Berau district, East Kalimantan province. The method used in this research is a quantitative research method. Multivariate analysis is used in analyzing research, involving variables in a number more than or equal to three variables. WarpPLS is mutivariate based and can analyze structural equation modeling (SEM). The results of the research show that corporate social responsibility (CSR) has a negative and significant effect on regional financial independence, PT Berau Coal's CSR program has a positive and positive effect. significant impact on regional development, tourism development that has been carried out has proven to have a positive and significant effect on regional financial independence. The existence of the tourism industry in Berau district has increased regional development. Regional financial independence will become more independent if regional original income (PAD) contributes to funding, regional development is getting bigger.